2018
DOI: 10.1002/jcp.26823
|View full text |Cite
|
Sign up to set email alerts
|

PTBP1 promotes the growth of breast cancer cells through the PTEN/Akt pathway and autophagy

Abstract: Invasion and migration is the hallmark of malignant tumors as well as the major cause for breast cancer death. The polypyrimidine tract binding, PTB, protein serves as an important model for understanding how RNA binding proteins affect proliferation and invasion and how changes in the expression of these proteins can control complex programs of tumorigenesis. We have investigated some roles of polypyrimidine tract binding protein 1 (PTBP1) in human breast cancer. We found that PTBP1 was upregulated in breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 24 publications
4
60
0
1
Order By: Relevance
“…We also added primers for an isoform of HNRNPK with exon 8 inclusion which was sequenced in saliva ( Figure 1 c and Supplementary Figure S1b–g ). Five out of the six splicing factors have been shown before to be overexpressed in breast cancer: HNRNPA1 [ 33 ], HNRNPA2B1 [ 34 , 35 ], HNRNPK [ 36 , 37 ], PTBP1 [ 38 , 39 ] and SRSF6 [ 40 , 41 , 42 ]. For normalization we chose PPIA, which is routinely used as an endogenous control in real-time experiments [ 43 ] and we have found it to be highly abundant relative to the other genes sequenced, with a number of 197 reads in cell-free RNA from saliva ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also added primers for an isoform of HNRNPK with exon 8 inclusion which was sequenced in saliva ( Figure 1 c and Supplementary Figure S1b–g ). Five out of the six splicing factors have been shown before to be overexpressed in breast cancer: HNRNPA1 [ 33 ], HNRNPA2B1 [ 34 , 35 ], HNRNPK [ 36 , 37 ], PTBP1 [ 38 , 39 ] and SRSF6 [ 40 , 41 , 42 ]. For normalization we chose PPIA, which is routinely used as an endogenous control in real-time experiments [ 43 ] and we have found it to be highly abundant relative to the other genes sequenced, with a number of 197 reads in cell-free RNA from saliva ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that using 12 such isoforms as biomarkers can distinguish a breast cancer tumor from normal tissue and moreover specify the grade level of the tumor [32]. Many splicing factors have been shown to have a role in breast cancer and to promote its progression, including SRSF1 [30,47,48], SRSF3 [49], SRSF5 [50], SRSF6 [40][41][42], SRSF10 [51], HNRNPA1 [33], HNRNPA2B1 [34,35,52], HNRNPM [53], HNRNPK [36,37], HNRNPL [54], RBFOX2 [55], ESRP1/2 [55], PTBP1 [38,39] RBM5/10 [56], Sam68 [57] and FOX2 [58]. Since our sequencing of saliva RNA identified 28 splicing factors out of the known 71, we focused on this group as a possible marker.…”
Section: Discussionmentioning
confidence: 99%
“…hnRNPM regulates EMT in breast epithelial cells, in part by promoting splicing of the CD44s isoform, and by altering TGF-β signaling (Xu et al, 2014). PTBP1-OE increases proliferation, anchorageindependent growth, and invasion in cancer cell lines (He et al, 2014;Wang et al, 2008), and PTBP1-KD in breast cancer cells had the opposite effect (Wang et al, 2018). Furthermore, PRPF8-and PRPF38A-KD, or treatment with the spliceosome inhibitor E7107, inhibits growth of TNBC cells and patient-derived TNBC xenografts (Chan et al, 2017).…”
Section: Rna-binding Proteins As Breast-cancer Driversmentioning
confidence: 99%
“…Studies have shown that autophagy is involved in regulating the growth and development of breast cancer [ 16 , 17 ]. The autophagy protein Beclin-1 serves as a tumor suppressor or tumor promoter in a context-dependent manner [ 18 ].…”
Section: Introductionmentioning
confidence: 99%